Water Hardness Removal Using Wheat Straw and Rice Husk Ash Properties - Kharel, Hari Lal; Sharma, Ram Kumar; Kandel, Tanka Prasad (Nepal Journal of Science and Technology, 2016)
This study examined potential of using wheat straw ash (WSA) and rice husk ash (RHA) to remove hardness of natural and hardness enriched synthetic water samples. Eight water samples (both natural and synthetic) with hardness ranging from 236 to 580 mg/l were treated with 10 different doses of WSA and RHA ranging from 2.5 to 25 g ash l–1 at regular increment of 2.5 g and one sample was included as control (no ash addition). Water hardness, hardness removal efficiency and pH changes of the treated water samples were measured. Hardness removal efficiency and pH of water increased with increasing doses of ash. Maximum removal was achieved at 17.5 g/l and 22.5 g/l for WSA and RHA, respectively, and further ash addition did not change the hardness. Maximum removal efficiency of WSA was 81% (i.e. 67 mg/g) and RHA was 58% (i.e. 44 mg/g). Higher hardness removal efficiency of WSA was due to presence of higher concentrations of alkali metal oxides. As similar to removal efficiency, WSA also increased pH of water samples relative to RHA. Maximum pH of 11.2 and 10.2 was respectively for WHA and RSA at the highest dose of ash (25 g/l). The results thus indicate that locally available ashes from agricultural sources may be useful in hardness removal process, however, softened cannot be used as drinking water due to the high level of alkalinity.